Mainstreaming climate change adaptation into pro-poor development initiatives: evidence from local economic development programmes in Ghana. (9th August 2021) - Ahenkan, Albert; Chutab, David Nawiene; Boon, Emmanuel Kwesi
ABSTRACT: Climate change remains a serious threat to climate sensitive pro-poor development interventions in the Pru District of Ghana. This study examined how climate change impacts on Local Economic Development (LED) interventions, the extent to which climate change adaptation (CCA) initiatives are integrated into LED and the challenges associated with the mainstreaming process. Qualitative research design and purposive sampling was used to collect data from 28 respondents at the Pru District Assembly with an interview guide. The results show that climate change adversely affects the following LED programmes; beekeeping, micro-credit for agricultural development programme, and fishing net and outboard motor programmes. The findings further indicate that climate-smart Agriculture, aquaculture (Fish Cage Culture) and Sustainable natural resource utilization and management the CCA initiatives mainstreamed into pro-poor LED in the Pru District to reduce the inevitable impacts of climate change. The study identified multifaceted challenges militating against CCA mainstreaming in the District to include inadequate resources for CCA, inactive stakeholder and institutional collaboration, and lack of continuity of CCA programmes. This paper recommends strong government support for CCA programmes, commitment of adequate resources and effective stakeholder and institutional collaboration. The paper concludes that effective integration of CCA into pro-poor LED is a panacea to achieving sustainable local development.